Determinants of women participation in income generating activities: Evidence from Ethiopia - Abera Alemu; Tesfaye Woltamo; Aklilu Abuto (Journal of Innovation and Entrepreneurship, 2022)
This paper aims to examine the major determinants and challenges of women's participation in income-generating activities focusing on rural women of Ethiopia. To carry out this study, both primary and secondary data were used. Randomly selected 161 households were the source of primary data for this study. Secondary data were collected from the review of related literature. A binary logistic regression econometric model was implemented to identify major determinants of women's participation in income-generating activities. The finding of this study revealed that in the study area, women are not allowed by their husbands to participate in high-income earning activities. They are considered a housewife and only husband are expected to participate in high income-generating activities due to the local customs. In the study area, women's participation in the income-generating activity is determined by age, husband's education, women's education, family size, land size, market distance, livestock holding, and access to credit. This paper contributes to the literature on women's participation challenges in income-generating activities, giving emphasis to rural women's perspectives. It provides the basis for further studies aimed at challenges hindering women's participation in high-income earning activities, particularly in developing countries.
Keywords: 650; Income generating activities; Determinants; Women; Logistic regression model